A Meta-Cognitive Approach to Predicting Hurricane Evacuation Behavior. Issue 1 (2nd January 2020) - Goldberg, Matthew H.; Marlon, Jennifer R.; Rosenthal, Seth A.; Leiserowitz, Anthony
ABSTRACT: As hurricanes intensify and more people are at risk, there is a clear need to understand the evacuation behavior of coastal residents. Of particular relevance is the role of past experience in evacuation decisions, about which evidence is mixed. In the current study, we use the Meta-Cognitive Model (MCM) to show that expectations of future hurricane evacuation are strongly predicted by the combination of past behavior and confidence in that past behavior. Specifically, we show that people who evacuated in the past are substantially more likely to expect to do so in the future when they have high confidence in their past decision to evacuate. Likewise, people who did not evacuate are substantially less likely to expect to evacuate in the future when they have high confidence in their past decision. This pattern was consistent across all hurricane intensities tested and extended to risk perceptions of future hurricanes. These findings have implications for risk communication about impending extreme weather events.